Developing public managers for a changing world - Majgaard, Klaus; Ry Nielsen, J. C.; Quin, Brid; Raine, John W. (Critical perspectives on international public sector ;, 2016)
Volume 5 of Critical Perspectives in International Public Sector Management is comprised of three parts. The need for experimental learning in public management development, experimental learning formats and innovative teaching and transfer and value creation.